2017
DOI: 10.4103/eus.eus_48_17
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial ultrasonography using a guide sheath technique for diagnosis of peripheral pulmonary lesions

Abstract: Endobronchial ultrasonography using a guide sheath (EBUS-GS) is a novel method used for collecting peripheral pulmonary lesion (PPL) samples. EBUS-GS is performed by introducing a guide sheath-covered miniprobe into the target bronchus and then withdrawing the miniprobe after lesion detection, leaving the guide sheath in situ as a working channel for obtaining lesion samples. EBUS-GS can improve PPL diagnosis rates and be used for obtaining specimens for molecular analysis. In this review, we discuss the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
1
18
0
1
Order By: Relevance
“…The literature reported that the total complication rate was 0−6.7%. The most common complication is pneumothorax, with an incidence of 0−7.5%, only 0.6% of patients need chest tube drainage, and the incidence of infection is about 0.5% ( 6 , 17 , 24 , 25 ). No patients with massive bleeding or operation-related deaths have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature reported that the total complication rate was 0−6.7%. The most common complication is pneumothorax, with an incidence of 0−7.5%, only 0.6% of patients need chest tube drainage, and the incidence of infection is about 0.5% ( 6 , 17 , 24 , 25 ). No patients with massive bleeding or operation-related deaths have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of these lesions is of great importance to reduce mortality owing to lung cancer ( 5 ). In recent years, endobronchial ultrasonography with guide sheath (EBUS-GS) has produced favorable results in the diagnosis of PPLs ( 6 ). However, EBUS-GS is only designed to confirm arrival at the lesion, fluoroscopy is still needed for guidance before the confirmation ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic yield of radial miniprobe is 60-70% when it used alone and increased until 84% with fluoroscopic guide and when was used in combination with virtual bronchoscopic navigation the overall diagnostic yield increased to 63.3-84%. 11,17 side the lesion (Figure 2, 3, 4). Bronchus sign is associated with the diagnostic sensitivity of miniprobe.…”
Section: Fluoroscopy Guidancementioning
confidence: 96%
“…The complication rates were lower (0% to 7.4%) than CT-guided TTNB [ 56 - 58 ]. Pneumothorax occurred in 1.0% of the patients [ 59 ], and bleeding, infection, and breaking of radial probes can occur in some cases [ 58 ].…”
Section: Endobronchial Ultrasound and A Guide Sheathmentioning
confidence: 99%